MANAJEMEN STRATEGI KEPALA SEKOLAH DALAM MENINGKATKAN KOMPETENSI GURU DI SMA NEGERI 2 PINRANG - Muhaeminah, Ummu; kamalia; Jannah, Miftahul; Ramadani, Alfani (IAIN Parepare, 2024)
This Research examines about the principal’s strategic management in improving teacher competence at SMA Negeri 2 Pinrang. The principal’s strategic management plays a role in decision making that is fundamental. The research method usedin this research is qualitative with the type of field study research. Techniques data collection in this study are observation, interview , and documentation. The results showed that the strategy developed by SMA Negeri 2 Pinrang aims to involve all teachers in the planning process, ensuring they have good skills to overcome the learning media problems. The role of the principal in improving competence of teachers at school is very important to be carried out through various platforms such as Merdeka mengajar platform. After the implementation is carried out, the evaluation is needed to be able to determine the success to what extent the need for teacher competency development. The principal also provides services to teacher to always improve the competencies prossessed by each teacher and provide digital space as a forum fot teachers to exchange ideas with each other. Provide digital space a forum for teachers to exchange ideas and knowledge to improve their competence. And knowledge to improve their competence.